2003
DOI: 10.1007/s11664-003-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of Cu-Sn intermetallic thin films

Abstract: Intermetallic compounds (IMCs) are formed as a result of interaction between solder and metallization to form joints in electronic packaging. These joints provide mechanical and electrical contacts between components. The knowledge of fracture strength of the IMCs will facilitate predicting the overall joint property, as it is more disposed to failure at the joint compared to the solder because of its brittle characteristics. The salient feature of this paper is the measurement of the fracture toughness and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…These values are higher than the reported fracture toughness of pure IMCs [30][31][32][33][34]. For example, the fracture toughness of Cu 6 Sn 5 IMC was reported to be 55.9±7.3 J/m 2 in [33].…”
Section: Source Of the Fracture Energy And Its Degradationmentioning
confidence: 77%
“…These values are higher than the reported fracture toughness of pure IMCs [30][31][32][33][34]. For example, the fracture toughness of Cu 6 Sn 5 IMC was reported to be 55.9±7.3 J/m 2 in [33].…”
Section: Source Of the Fracture Energy And Its Degradationmentioning
confidence: 77%
“…s when the whole body is elastic. From the experimental findings of Balakrsinan et al and Fields et al [18][19][20][21], it was found that critical values for the…”
Section: Effect Of Crack Location Relative To the Interfacementioning
confidence: 99%
“…[5][6][7][8][9][10] Deng et al measured Young's moduli of Cu 3 Sn and Cu 6 Sn 5 in Cu/solder joints by nanoindentation. 5 They also extracted the yield stress of the IMCs from loading-unloading curves in nanoindentation processes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Balakrisnan et al made thin-film beam specimens of Cu 3 Sn and Cu 6 Sn 5 by sputtering and conducted buckling tests to measure the fracture toughness of the IMCs. 7 Jiang et al made a micropillar specimen of Cu 6 Sn 5 using a focused ion beam (FIB) system and conducted compression tests using a nanoindenter with a flat tip to obtain the stress-strain curve of Cu 6 Sn 5 . 8 FEA has also been conducted considering the Cu/ Sn IMCs in solder joints.…”
Section: Introductionmentioning
confidence: 99%